2001
DOI: 10.1002/ptr.738
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Malian medicinal plants for antifungal, larvicidal, molluscicidal, antioxidant and radical scavenging activities

Abstract: A total of 78 different extracts from 20 medicinal plants belonging to 14 plant families from Mali were tested for their antifungal, larvicidal, molluscicidal, antioxidant and radical scavenging activities. Dichloromethane, methanol, water and ethanol extracts were used. TLC autobiography for antifungal activity was run with Cladosporium cucumerinum and Candida albicans. Extracts were also tested on the larvae of the mosquitoes Aedes aegypti, Anopheles gambiae and Culex quinquefasciatus. Molluscicidal activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 17 publications
(15 reference statements)
2
62
0
1
Order By: Relevance
“…Okunji et al (1996) reported fungistatic and fungicidal activity of spiroconazole A, a saponin compound from Dracaena mannii and D. arborea. In a related study by Diallo et al (2001), extracts from Cussonia barteri and Lannea velutina gave a positive response against C. albicans, thus corroborating the anticandida activity of C. arborea and L. shimperi observed in the present study. R. vomitoria has also been reported to possess antifungal activities (ENVIS (Environmental Information System) Center, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Okunji et al (1996) reported fungistatic and fungicidal activity of spiroconazole A, a saponin compound from Dracaena mannii and D. arborea. In a related study by Diallo et al (2001), extracts from Cussonia barteri and Lannea velutina gave a positive response against C. albicans, thus corroborating the anticandida activity of C. arborea and L. shimperi observed in the present study. R. vomitoria has also been reported to possess antifungal activities (ENVIS (Environmental Information System) Center, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…With fragments ions at m/z 203, 125 and 108, this compound shared characteristics of catechin and / or epicatechin, flavonids monomers of the condensed tannins. The presence of these flavonoids has been reported previously in other species from Rhamnaceae family (Boligon et al, 2012) and particularly in the genus Ziziphus, for instance Z. lotus L. (Diallo et al, 2004;Borgi et al, 2007;Soumia, 2009). In their study, Berthod et al (1999) stress the difficulty of precisely identifying those compounds whose polymer chains of different lengths are difficult to separate.…”
Section: Phytochemical Analysis Of Crude Extract Of Z Mucronatasupporting
confidence: 64%
“…In recent times, studies on the activity of plant extracts towards Aedes sp. larvae from different parts of the world, such as, North America (Bergeron et al, 1996), Argentina, Bolivia, Brasil and Peru (Chantraine et al, 1998;Ciccia et al, 2000;Macedo et al, 1997), Trinidade and Tobago (Chariandy et al, 1999), Mali (Diallo et al, 2001), Negev Desert (Sathiyamoorthy et al, 1997) and Africa (Marston et al, 1993), among others, have been published and have revealed numerous examples of active plant extracts representing diverse taxonomic groups. More systematic and directed studies have revealed a number of very active plant extracts, essential oils, and isolated larvicidal phytochemicals (Bandara et al, 2000;Bernard et al, 1995;Hostettmann & Potterat, 1997;Latha & Ammini, 2000;Lee, 2000;Oberlies et al, 1998;Park et al, 2002;Pushpalatha & Muthukrishnan, 1999;Rahuman et al, 2000;Sharma et al, 1998;Thorsell et al, 1998).…”
Section: Introductionmentioning
confidence: 99%